Custom fabricated acrylic vaginal stent as an adjunct to surgical creation of neovagina for a young female with isolated vaginal agenesis - Manu Rathee; Priyanka Boora; Renu Kundu (Wolters Kluwer Medknow Publications, 2014)
Vaginal agenesis is one of the major congenital anomalies of the female genital tract. It may present either as an isolated developmental defect or within a complex of more extensive anomalies. Most commonly it is associated with Mayer-Rokitansky-Kόster-Hauser (MRKH) syndrome. The correction of vaginal agenesis requires the creation of a neovaginal cavity that is dissected between the bladder and the rectum. After reconstruction of space for vagina surgically, a long-term vaginal stent use is required to maintain vaginal width and depth and to prevent contraction. In this article is presented a case of nonsyndromic agenesis of vagina in a 14-year-old girl and its surgical management using custom fabricated acrylic vaginal stent.